Epidermal micromorphology in Dioon: did volcanism constrain Dioon evolution?. (31st August 2015) - Barone Lumaga, Maria Rosaria; Coiro, Mario; Truernit, Elisabeth; Erdei, Boglárka; De Luca, Paolo
<x xml:space="preserve">Abstract</x> The genus Dioon occupies an important phylogenetic position as sister to the other Zamiaceae. However, its epidermal morphology is still poorly known. We employed scanning and transmission electron microscopy, confocal microscopy and light microscopy to examine the epidermal and cuticular morphology of 12 of the 14 currently recognized species of Dioon, examining cultivated plants and herbarium specimens. Epidermal characters separate Dioon quite clearly from the other genera of the cycads. Within the genus, the major subgroups can be distinguished by their epidermal morphology. Some characters, such as the degree of stomatal protection, reflect ecological specializations in species within the subgroups. Several epidermal characters of the crown group Dioon seem to be absent in the Cenozoic fossils usually associated with the genus, which have been used as calibrations in many recent molecular dating analyses. The presence of similar characters in a Mesozoic fossil adapted to volcanic stress offers a new key in the interpretation of Dioon evolution. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 179, 236–254.